Sensitivity Analysis of Uncertain Material RC Structure and Soil Parameters on Seismic Response of Soil-Structure Interaction Systems - Mekki, Mohammed; Zoutat, Meriem; Elachachi, Sidi Mohammed; Hemsas, Miloud (Periodica Polytechnica Civil Engineering, 2022)
In seismic performance based design context, engineers are faced to a difficult task to estimate the response of soil-structure interaction (SSI) systems. To accomplish this task successfully, all sources of random and epistemic uncertainties should be taken into account. However, the uncertain parameters have not the same influence on the model response; a sensitivity analysis is therefore required. This article treats the two following aspects: the first one is to perform a sensitivity analysis on all the parameters in order to study their influence on the structural response. The uncertainties effect is done by studying the sensitivity of the maximum structure displacement towards the used materials parameters variation (fc’, εc0, εcu, Es, fsy, α, εsu, A, ξ) and soil properties (ξg, ν) on the SSI seismic response. This study consists of determining, quantifying and analyzing how the outputs of the N2-SSI model are affected by input variables fluctuations. The second aspect is analysing the SSI system response by considering the correlation between the parameters (shear wave velocity and soil damping) and the influence of the lack knowledge of the uncertainties due to this correlation. The results of the sensitivity analysis indicate that the response of the structure is very sensitive to the concrete and steel parameters for larger values of the shear wave velocity. While, the soil damping and Poisson’s ratio in the case of soil with shear wave velocity of 90 m/s, are the main inputs with the greatest influence on the maximum displacement output.